Pemerkosaan Anak di Bawah Umur Ditinjau dari Moral Seksualitas Perkawinan dan Keluarga - Pasati, Yohanes Dwi Penta (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
Every human action always begins with various considerations to arrive at a decision. These studies become an interesting discussion in the study of morals, especially the moral sexuality of marriage. The moral of marital sexuality itself is not only talking about the biological relationship of husband and wife, but also a deep reflection of the integrity of the self as a man and a woman. Manhood and womanhood are understood as perfect so that it leads someone to accept creation, respect, and even protect the integrity of others.